Management of hazardous goods transported by land in Singapore - Lee, Yin Onn. (2008)
This thesis examines the coverage and adequacy of the safety measures in transport and handling of Hazmat in Singapore. Results of a survey of the local logistics companies involved in dangerous goods transport were analysed.